Structural Basis of Human Dimeric α-Amino-β-Carboxymuconate-ε-Semialdehyde Decarboxylase Inhibition With TES-1025 - Cianci, Michele; Giacchè, Nicola; Cialabrini, Lucia; Carotti, Andrea; Liscio, Paride; Rosatelli, Emiliano; De Franco, Francesca; Gasparrini, Massimiliano; Robertson, Janet; Amici, Adolfo; Raffaelli, Nadia; Pellicciari, Roberto (Frontiers in Molecular Biosciences, 2022)
Human α-amino-β-carboxymuconate-ε-semialdehyde decarboxylase (ACMSD) stands at a branch point of the de novo NAD+ synthesis pathway and plays an important role in maintaining NAD+ homeostasis. It has been recently identified as a novel therapeutic target for a wide range of diseases, including inflammatory, metabolic disorders, and aging. So far, in absence of potent and selective enzyme inhibitors, only a crystal structure of the complex of human dimeric ACMSD with pseudo-substrate dipicolinic acid has been resolved. In this study, we report the crystal structure of the complex of human dimeric ACMSD with TES-1025, the first nanomolar inhibitor of this target, which shows a binding conformation different from the previously published predicted binding mode obtained by docking experiments. The inhibitor has a Ki value of 0.85±0.22 nM, and binds in the catalytic site, interacting with the Zn2+ metal ion and with residues belonging to both chains of the dimer. The results provide new structural information about the mechanism of inhibition exerted by a novel class of compounds on ACMSD enzyme, a novel therapeutic target for liver and kidney diseases.